2003
DOI: 10.1099/vir.0.19101-0
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal region of the movement protein of Cowpea mosaic virus is involved in binding to the large but not to the small coat protein

Abstract: Cowpea mosaic virus (CPMV) moves from cell to cell as virus particles which are translocated through a plasmodesmata-penetrating transport tubule made up of viral movement protein (MP) copies. To gain further insight into the roles of the viral MP and capsid proteins (CP) in virus movement, full-length and truncated forms of the MP were expressed in insect cells using the baculovirus expression system. Using ELISA and blot overlay assays, affinity purified MP was shown to bind specifically to intact CPMV virio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…The MP-CP interactions necessary for virus local movement have already been described for a number of positive-strand RNA viruses (18). Evidence for direct binding between CP and MP both in vitro (Maize streak virus and Cowpea mosaic virus [CPMV]) and in vivo (Maize streak virus) has been reported (6,21). Moreover, it has been shown that CPMV virions are transported through tubules formed with CPMV MP via MP-CP interactions and deposited in the adjacent cell (37).…”
Section: Discussionmentioning
confidence: 96%
“…The MP-CP interactions necessary for virus local movement have already been described for a number of positive-strand RNA viruses (18). Evidence for direct binding between CP and MP both in vitro (Maize streak virus and Cowpea mosaic virus [CPMV]) and in vivo (Maize streak virus) has been reported (6,21). Moreover, it has been shown that CPMV virions are transported through tubules formed with CPMV MP via MP-CP interactions and deposited in the adjacent cell (37).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the observation that MP-YFP was immobile within tubules suggested that tubules consisted of a stable MP multimer. Previously, interaction between MP subunits has been shown to occur in vitro using a blot overlay assay (Carvalho et al, 2003), and .…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy analysis revealed that these tubules were morphologically indistinguishable from tubules made by non-fused MP, except that GFP, which was fused to the C terminus of MP and thus present inside the tubule (Carvalho et al, 2003), prevented the incorporation of virus particles (Gopinath et al, 2003). MP-GFP also accumulated in peripheral punctate spots in protoplasts & Palukaitis, 1999; Heinlein et al, 1998;Huang et al, 2000; Satoh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate potential rNTP-binding properties of CPMV MP, GTP-coupled agarose beads (Sigma), prewashed three times with binding buffer (24), were incubated for 60 min at 4°C with 5 g of purified wild-type MP (wtMP; prepared as described previously [3]). The beads were then pelleted by centrifugation (5 min at 18,000 Ï« g) and washed three times with binding buffer to remove unbound proteins.…”
mentioning
confidence: 99%